OP05 Medium term outcome of de novo autoimmune hepatitis after liver transplantation in children; a single centre experience. (16th November 2010) - Hii, M; Grammatikopoulus, A; Hadzic, N; Rela, M; Mieli-Vergani, G; Vergani, D
Abstract : Introduction: Post-transplant de novo autoimmune hepatitis (dn-AIH) is a cause of late graft dysfunction characterized by hypergammaglobulinemia, elevated titres of serum auto-antibodies, histological features of chronic hepatitis with portal and periportal inflammation with lymphocytes and plasma cells, and clinical response to the treatment for classical autoimmune liver disease with steroids and azathioprine (aza) or mycophenolate mofetil (MMF). Aim: To establish the prevalence and the medium term outcome of dn-AIH. Method: Retrospective review of case notes of patients who were diagnosed with dn-AIH since the initial case description in 1995 to date. Results: Thirty children (17, 57% female) were diagnosed using the above criteria. Overall incidence was around 5 %. The aetiologies leading to liver transplant (LT) were: biliary atresia (16), Alagille syndrome (3), alpha 1-antitrypsin deficiency (3), progressive familial intrahepatic cholestasis (2), glycogen storage disease type 1b (2), familial hypercholesterolemia (1), non-A-E hepatitis (1), Crigler-Najjar syndrome type 1 (1) and cryptogenic end-stage liver disease (1). Four (13.3%) patients received whole grafts, while the remainder received segmental grafts, including 2 (6.7%) auxiliary and 4 (13.3%) living-related grafts. The median age at diagnosis of dn-AIH was 11.2 years (range, 2.6–19.3). The median post-LT interval to develop dn-AIH was 4.1 years (range, 0.2–11.0). The median follow up after diagnosis of dn-AIH was 8.2 years (range, 0.3–14.8). Auto-antibodies detected included ANA (n=21), SMA (n=20), anti-mitochondrial antibody (n=4), anti-LKM (n=2) and anti-liver cytosol-1 (n=1). Immunosuppressive regimens at the time of dn-AIH diagnosis included: CyA/aza/pred (9), Tac/aza/pred (6), Tac/MMF/pred (6), CyA/MMF/pred (4), and Tac/pred (5). Dn-AIH was treated with increased dose of steroids and increased dose or addition of aza or MMF. Eleven (36.7%) patients did not adhere to medications during follow up. Of these, 10 (33.3%) developed chronic liver failure (CLF) and 6 (20%) required re-LT, after a median period of 5.8 years. Two (6.7%), including a non-adherent child, died with multiorgan failure after re-LT for CLF. Of 4 further children with CLF, 3 (10%), all with history of non-adherence, are currently listed for re-LT, while one (3.3%) is stable. Twenty patients (66.6%) have no evidence of graft dysfunction. Conclusion: The medium-term prognosis of dn-AIH is severe in a considerable proportion of patients and is determined by adherence to medications.